From Tea to Kumiss: Coding “Li-Qun-Du” Care Scripts into Belt-and-Road Tunnel Performance - Cheng Che (Research Retrieval and Academic Letters, 2025)
At the moment of the in-depth reconstruction of the global value chain and the high-quality joint construction of the “Belt and Road”, Chinese engineering construction companies are moving from “equipment going to sea” and “engineering going to sea” to “concept going to sea” and “culture going to sea”. The Luang Prabang station building of the China-Laos Railway, the Karawang beam yard of the Jakarta-Bandung High-Speed Railway, and the Novi Sad maintenance center of the Hungary-Serbia Railway are no longer just a physical collection of concrete and steel rails, but have become a place where the memory, institutional logic and emotional structure of different civilizations meet. However, the larger the scale of assets and the more diverse the stakeholders, the exponential increase in the coefficient of cultural friction: in the same project email, the Chinese side reads as “efficiency first,” but the foreign side regards it as “risk disregard”; in the same Gantt chart, the Chinese side sees “mission must be achieved,” but the foreign side questions “erosion of life.” The western cross-cultural framework, which has traditionally been based on Hofstede’s Cultural Dimensions or Kluckhohn’s value orientation, simplifies cultural differences into calibrable "distances", but it is difficult to explain why the two central and south teams with similar scores in the collectivist dimension will still fall into a protracted tug-of-war over “who has the right to stop safe operations.” The crux is that the Western paradigm presupposes the underlying order of “rule-contract-individual", while Chinese engineering companies carry the civilized gene of ”relationship-affection-community". When the two meet in the high-coupling and high-stakes field of construction sites, there will inevitably be a mismatch of “the concept is sound, but the mindsets do not align”.